Maximisation of weather radar network coverage based on accelerated particle swarm optimisation. (2015) - Boudjemaa, Redouane
This work proposes an approach to the optimal placement of a weather radar network based on an accelerated particle swarm optimisation. Given a finite number of weather radars, a network is produced such that the geographical coverage area of the radars is maximised. By taking into account several constraints such as terrain blockage and radar beam elevation, the problem is formulated into an optimisation process. By transforming the search space into a gridded system, a reduction in the number of possible combinations of radar networks is achieved making the problem manageable in size. Numerical results show a good convergence to an acceptable solutions based on the percentage of area covered. The results obtained by the proposed method were compared to a genetic algorithm-based approach. The proposed approach can serve as an analysis tool for a decision support system to assist meteorologist in the selection of future prime sites for the installation of weather radars.